2017
DOI: 10.5530/jyp.2017.9.62
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Frequency Adverse Drug Reactions in Tertiary Care Hospital of Kolkata, West Bengal, India

Abstract: (ADR) is a severe drawback of the therapeutics in the recent world. Pharmacovigilance is the practice of keeping records of these ADRs. The practice of pharmacovigilance is thus essential to decrease the incidence of adverse drug reaction occurring from different drugs. This is an open access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as the author is credite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
(20 reference statements)
3
11
0
Order By: Relevance
“…This was in concurrence with other similar studies by Adhikari A et al, Raja S et al, Venkatasubbaiah M, and Rani J. 13,14,17,19,20 However, Prashanthi B et al, observed anti-inflammatory agents and immunosuppressive drugs to be the most common cause of ADRs. 21…”
Section: Discussionsupporting
confidence: 90%
“…This was in concurrence with other similar studies by Adhikari A et al, Raja S et al, Venkatasubbaiah M, and Rani J. 13,14,17,19,20 However, Prashanthi B et al, observed anti-inflammatory agents and immunosuppressive drugs to be the most common cause of ADRs. 21…”
Section: Discussionsupporting
confidence: 90%
“…A drug or medicine is a pharmaceutical product of chemical substance used in the prevention, treatment, cure of disease or for the modification of physiological function or pathological state in the benefit of the recipient". 3,4 Drugs may be used for a limited duration, or on a regular basis for chronic disorders. Apart from all the benefits of the drugs, the adverse reactions and adverse events associated with them are most common.…”
mentioning
confidence: 99%
“…Adverse drug reaction can be defined as "an appreciably harmful or unpleasant reaction, resulting from an intervention related to the use of a medicinal product, which predicts hazard from future administration and warrants prevention or specific treatment, or alteration of the dosage regimen, or withdrawal of the product". 3 They are usually preventable, cause of illness, which may require modifying the dosage regimen or discontinuing a medication or prolongation of hospitalization. But sometimes it results in disability or can be lifethreatening even cause death.…”
mentioning
confidence: 99%
See 2 more Smart Citations